A Human Rights Approach to Examine Indonesia’s Social Forestry Policies - Alfirdaus, Laila Kholid; Mangkunegara, RM Ahmada -; Fitriah, Fitriah (University of Jember, 2024)
This research evaluates social forestry policies in Indonesia through the lens of human rights, focusing on the experiences of forest farmers within local communities. While social forestry is intended to empower marginalized groups, promote forest conservation, and ensure equitable access to resources, its implementation exposes systemic barriers that undermine the human rights of local communities. Such issues restrict the right of affected marginalised communities such as indigenous peoples and women. This exclusion perpetuates socio-economic inequalities and undermines their fundamental rights to fair participation and equitable resource distribution. Based on this observation, the study highlights significant gaps in policy implementation. By drawing comparisons with community-based forest management models in other countries, the study underscores the importance of collaborative governance and equitable benefit-sharing mechanisms. The findings emphasize the need for a rights-based, integrated approach to social forestry that prioritizes transparency, inclusivity, and the empowerment of marginalized groups. Aligning local implementation with global human rights and conservation goals is essential for achieving equitable, sustainable, and socially just outcomes in Indonesia's social forestry initiatives. Keywords: Human Rights, Social Forestry, Indonesia, Marginalised Communities, Indigenous People